Pengaruh Profitabilitas dan Ukuran Perusahaan terhadap Nilai Perusahaan melalui Struktur Modal sebagai Variabel Intervening (Studi pada Perusahaan Sub-sektor Asuransi yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2020-2024) - Melisa Putri; Elfiswandi .; Rindy Citra Dewi (GLOBAL SCIENTS PUBLISHER, 2026)
This research aims to analyze and estimate the influence of profitability and company size on company value through capital structure using a purposive sampling method with a sample of 13 companies and the analysis method used is multiple linear regression analysis and path analysis (path analysis) using SPSS 26.Based on the results of the multiple regression analysis carried out, it can be concluded that profitability partially does not have a significant effect on capital structure, company size partially does not have a significant effect on capital structure, profitability partially does not have a significant effect on company value, company size partially has a significant effect on company value and capital structure partially does not have a significant effect on company value. Based on the results of path analysis tests (path analysis), it shows that capital structure is able to mediate the relationship between the influence of profitability on company value and structure is able to mediate the relationship between the influence of company size on company value.